Decoration of T-independent antigen with ligands for CD22 and Siglec-G can suppress immunity and induce B cell tolerance in vivo - Duong, Bao Hoa (The Rockefeller University Press, 2010)
Autoreactive B lymphocytes first encountering self-antigens in peripheral tissues are normally regulated by induction of anergy or apoptosis. According to the “two-signal” model, antigen recognition alone should render B cells tolerant unless T cell help or inflammatory signals such as lipopolysaccharide are provided. However, no such signals seem necessary for responses to T-independent type 2 (TI-2) antigens, which are multimeric antigens lacking T cell epitopes and Toll-like receptor ligands. How then do mature B cells avoid making a TI-2–like response to multimeric self-antigens? We present evidence that TI-2 antigens decorated with ligands of inhibitory sialic acid–binding Ig-like lectins (siglecs) are poorly immunogenic and can induce tolerance to subsequent challenge with immunogenic antigen. Two siglecs, CD22 and Siglec-G, contributed to tolerance induction, preventing plasma cell differentiation or survival. Although mutations in CD22 and its signaling machinery have been associated with dysregulated B cell development and autoantibody production, previous analyses failed to identify a tolerance defect in antigen-specific mutant B cells. Our results support a role for siglecs in B cell self-/nonself-discrimination, namely suppressing responses to self-associated antigens while permitting rapid “missing self”–responses to unsialylated multimeric antigens. The results suggest use of siglec ligand antigen constructs as an approach for inducing tolerance.